Meeting of Chief Secretaries on Implementation of Economic Stimulus Measures Background Papers (Volume I) - Planning Commission (Planning Commission, 2009)
Holding interactions with larger construction agencies for their participation in PMGSY works for utilizing surplus capacity available with them in view of recession in real-estate sector. More effective contract management for ensuring timely completion of projects so that fresh capacity is freed up for executing new projects. In many states tendering process is taking as long as 6-7 months against prescribed norm of 3 months. Expeditious forest clearance for land required in some states especially, Himachal Pradesh and Uttarakhand. (d) Ensuring availability of land before project clearance. Road alignment should be finalized through ‘transect walk’ by associating the user community. Launching of a new sub-scheme under PMGSY for providing all weather connectivity to habitations with population less than 250 in hill states, tribal areas and desert areas and less than 500 in other areas in those states which have already achieved all weather road connectivity for all habitations as per norm prescribed under the existing PMGSY guideline.
Government of India
Government of India Planning Commission